Comparison of Thyroid Blood Flow and Uptake Indices Using Technetium-99m Pertechnetate in Patients with Graves’ Disease and Euthyroid Subjects - Javadi, Hamid (Mol Imaging Radionucl Ther, 2014)
Objective: The aim of the present study was to evaluate parameters of early blood flow (EBF) including duration of EBF, perfusion index (PI), uptake indexes 1 and 2 (UI1 and UI2) derived from dynamic thyroid scintigraphy in patients with Graves’ disease (GD), and euthyroid (EI). Maximum instant uptake and maximum uptake of the thyroid gland were also assessed. Methods: A total of 50 patients with GD and EI were included in this study. Each patient underwent two dynamic scans of 1-minute (20 images at 3 seconds) and 20-minute (20 images at 1 minute) with (99m)TcO4. The time-activity curve of a 1-minute scan was employed to derive EBF parameters; likewise, the time-activity curve of a 20-minute scan was used to determine maximum instant uptake, and the gradient of the curve from the 10th to 20th minute was used to assess maximum uptake. Results: Values of EBF duration, PI, UI1, UI2, and maximum instant uptake were significantly lower in patients with GD than in those with EI (p<0.05). The calculated gradient of the second half of the curves for all of the patients ranged from 0 to 0.88 and was significantly higher in patients with GD than in those with EI. Conclusion: Lower values of PI, UI1, UI2 and durations of EBF, along with faster maximum instant uptake in patients with GD in comparison to EI are indicators of a heightened desire for hyper-functioning thyroid glands of patients with GD to absorb (99m)TcO4. Additionally, because of the uprising gradient at the end of the 20-minute time-activity curve, a maximum thyroid uptake of (99m)TcO4 was achieved at more than 20 minutes after the radiopharmaceutical injection.